Equivalence of one-dimensional second-order linear finite difference operators. Issue 10 (2nd October 2016) - Miro, B.; Rose, D.; Valiquette, F.
Abstract : The direct, gauge and projective equivalence problems for one-dimensional second-order linear finite difference operators are solved using the method of equivariant moving frames.